Cash Reserve, CEO Health Risk, The Price Reaction Due to COVID-19 First Announcement on Leisure Industry - Muhammad Afif Arsyad; Cynthia Afriani Utama (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study investigates stock market reaction on leisure industries to first announcement of COVID-19 case which affected Indonesia on 2nd March 2020. The method of this research is event study and supported by multiple linear regression to analyze the relationship between market reaction and independent variables. This paper uses Fama French three-factor models to estimate expected return on firms due to the COVID-19 announcement. Based on a calculation of Cumulative abnormal returns, the stock of tourism industries has a more negative reaction towards a confirmed first case of COVID-19 compared to other industries. We also find that Indonesian firms with greater cash reserves experienced less negative returns while firms with higher leverage ratios were penalized more. Additionally, we don’t find that firms with CEOs who were exposed to significant health risks from COVID-19 experienced worse stock market performances.